2022
DOI: 10.1002/ldr.4314
|View full text |Cite
|
Sign up to set email alerts
|

The Eurasian crane (Grus grus) as an ecosystem engineer in grasslands: Conservation values, ecosystem services, and disservices related to a large iconic bird species

Abstract: Large bird species, such as cranes are involved in human‐wildlife conflicts as they often forage in croplands. The Eurasian crane (Grus grus) is a large bird species, protected across Europe, which, thanks to conservation programmes and its ability to utilise croplands for foraging, shows a strongly increasing population trend. This exaggerates the existing conflicts between crop farmers and cranes and is spilling over to natural habitats, where foraging by large flocks can lead to land degradation. No studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Thus, the investigated Grey Heron colony appears a prominent natural in situ experiment unfolding the changes in an engineered ecosystem in response to the excessive deposition of both biogenic elements (N, P) and toxic organics in the soil, as well as considerably reduced pH values compared to the presumably unaffected surrounding forest area. The above conditions are representative for both natural areas occupied with birds (Goc et al, 2005;Hobara et al, 2005;Kameda et al, 2006;Adamonytė et al, 2013;Klimaszyk et al, 2015;Klimaszyk and Rzymski, 2016;Guo et al, 2018;Matulevičiūtė et al, 2018;Veum et al, 2019;Al Shehhi and Muzaffar, 2021;Machač et al, 2022;Valkó et al, 2022) as well as agricultural environments (Bradbury et al, 2005;Minkina et al, 2022). Accordingly, considering the emergence of the bird colony around 2006 and its further expansion as an experimental input, one can currently observe an engineered ecosystem with accumulated alterations in soil biogeochemistry and consequent impact on the trees and other surrounding vegetation as an endpoint of a 15-year long natural experiment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the investigated Grey Heron colony appears a prominent natural in situ experiment unfolding the changes in an engineered ecosystem in response to the excessive deposition of both biogenic elements (N, P) and toxic organics in the soil, as well as considerably reduced pH values compared to the presumably unaffected surrounding forest area. The above conditions are representative for both natural areas occupied with birds (Goc et al, 2005;Hobara et al, 2005;Kameda et al, 2006;Adamonytė et al, 2013;Klimaszyk et al, 2015;Klimaszyk and Rzymski, 2016;Guo et al, 2018;Matulevičiūtė et al, 2018;Veum et al, 2019;Al Shehhi and Muzaffar, 2021;Machač et al, 2022;Valkó et al, 2022) as well as agricultural environments (Bradbury et al, 2005;Minkina et al, 2022). Accordingly, considering the emergence of the bird colony around 2006 and its further expansion as an experimental input, one can currently observe an engineered ecosystem with accumulated alterations in soil biogeochemistry and consequent impact on the trees and other surrounding vegetation as an endpoint of a 15-year long natural experiment.…”
Section: Discussionmentioning
confidence: 99%
“…Large bird colonies occupying relatively compact areas deposit excessive amounts of nutrients (Frederick and Powell, 1994;Ashworth et al, 2020), leading to considerable alterations in the soil geochemistry and microbiota, affecting the surrounding vegetation, and thus altogether considerably altering the local ecosystems (Sekercioglu, 2006;Whelan et al, 2015;Natusch et al, 2017;Lowney and Thomson, 2021;Grant et al, 2022;Hawke, 2022;Lowney and Thomson, 2022). For example, the impact of large birds like cormorants (Phalacrocorax carbo), Adélie penguins (Pygoscelis adeliae), Eurasian Crane (Grus grus) and Grey Heron (Ardea cinerea) has been intensively studied (Goc et al, 2005;Hobara et al, 2005;Kameda et al, 2006;Adamonytė et al, 2013;Klimaszyk et al, 2015;Klimaszyk and Rzymski, 2016;Guo et al, 2018;Matulevičiūtė et al, 2018;Veum et al, 2019;Al Shehhi and Muzaffar, 2021;Machač et al, 2022;Valkó et al, 2022). These birds form large colonies on coasts and forests leading to an intensive deposition of allochthonous substances in the local environment and consequent eutrophication, in turn altering the soil biogeochemistry, degrading the biodiversity and suppressing plants vegetation (Ishida, 1996;Anderson and Polis, 1999;Hobara et al, 2005;Kolb et al, 2012;Adamonytė et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Ecosystem engineer organisms create patches that differ from the surrounding matrix in their structure or ecosystem functions ( Jones, Lawton & Shachak, 1994 ). In this way they alter the resource distribution in the landscape ( Mallen-Cooper, Nakagawa & Eldridge, 2019 ; Neilly, Cale & Eldridge, 2022 ; Valkó et al, 2022 ). Previous syntheses on ecosystem engineers found that there are several factors determining the characteristics of the engineered patches, including the traits of the engineer, the habitat, climate and soil type ( Mallen-Cooper, Nakagawa & Eldridge, 2019 ; Root-Bernstein & Ebensperger, 2013 ).…”
Section: Introductionmentioning
confidence: 99%